CSC785: Philosophy of Computer Sciences / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2018)
Philosophy of Computer Science is a philosophical investigation at a level in which questions of knowledge (epistemology), existence (ontology), and value (ethics) are posed within the context of computer science. It seeks to address philosophical problems that arise from within the discipline of computer science. While real world processes amenable to modelling by computer are limitless, philosophy of computer science delineates the limits by putting forth models of human mind in terms of computer science.